The effect of low-temperature annealing of soft magnetic FeCo-2V alloy - Lau, Daniel Miang Hui (Nanyang Technological University, 2023)
FeCo-2V is a soft magnetic alloy that has high magnetic saturation and low coercivity, making it a prime choice for the aerospace industry. However, its brittleness limits its suitability for applications where mechanical properties are of high importance. Although some studies have explored the effect of low temperature heat treatment on FeCo-2V microstructure and alloy properties, none have investigated the impact of extended durations of heat treatment. In this study, the writer investigated the effect of extended durations of low temperature heat treatment on FeCo-2V microstructure, mechanical properties, and magnetic properties, including the degree of recrystallization. The results collected showed that, despite annealing durations of up to 900 hours at temperatures of 250 ℃ and below, FeCo-2V only underwent recovery and not recrystallization. The correlation between microstructure, alloy hardness, coercivity, and core loss were observed, and the significance of the impact of microstructure on alloy properties was highlighted. The findings from this study contribute to the understanding of the behaviour of FeCo-2V under extended low temperature heat treatment and can assist in future steps towards the development of new and improved processing strategies for this alloy.